Safety and effectiveness of the new P2Y12r inhibitor agents vs clopidogrel in ACS patients according to the geographic area: East Asia vs Europe - Giordana, Francesca; Montefusco, Antonio; D'Ascenzo, Fabrizio; Moretti, Claudio; Scarano, Silvia; Abu-Assi, Emad; Raposeiras-Roubín, Sergio; Henriques, Jose Paulo Simao; Saucedo, Jorge; González-Juanatey, José Ramón; Wilton, Stephen B; Kikkert, Wouter J; et al. (Elsevier BV, 2016)
Background In the setting of the Acute Coronary Syndrome (ACS), differences in response to prasugrel and ticagrelor between East Asian and European patients have not been investigated yet. Methods This is a sub-analysis of the “BleeMACS registry”. Patients admitted for ACS and underwent PCI from between 2012 and 2014 were stratified first according to their provenance, Europe vs. East Asia (China and Japan), and then by country. The adjusted rate of 1-year serious bleeding -safety end-point- and 1-year death/re-infarction -effectiveness endpoint- of the new P2Y12r inhibitors were compared. Results Data of 10004 patients in Europe and 2332 patients in East Asia were collected. At baseline prior stroke (6% vs 9%, p<0.001, respectively) and type of ACS (59% vs 71% STEMI, 11% vs 21% Unstable Angina) were significantly different among the groups. At 1year follow-up no difference in bleeding (3% vs 3%, p=0.84) was found, while the between group incidence of death/re-infarction was significantly higher in the European centers (9% vs 5%, p<0.001). At the multivariate analysis, ticagrelor decreases the risk of MACE (Europe: HR 0.5, CI 0.3–0.9; East Asia: HR 0.5, CI 0.2–0.9), despite of a higher risk of bleeding in Caucasians (HR 1.7, CI 1.1–2.6). Prasugrel reduces death/re-infarction (HR 0.4, CI 0.2–0.6), without increasing bleeding (HR 0.9, CI 0.5–1.3). Conclusions In the setting of the ACS, the new anti-platelets drugs appear to be safe and efficacious at mid-term follow-up independently from the geographic area. Prasugrel seems to have the best risk–benefit, while ticagrelor appears safer in East Asians.
Keywords: Acute coronary syndrome; Clopidogrel; Ethnicity; Platelet inhibitor; Prasugrel; P2Y12 receptor; Ticagrelor